Unravelling the Determinants of the Human Milk Microbiome in Allergic Women - Jie Ma; Debra J. Palmer; Ching Tat Lai; Donna T. Geddes; Lisa F. Stinson (Proceedings)
As some of the most common chronic diseases globally, allergic diseases have been associated with the gut microbiome composition of both children and adults [...]